Path algebras - Adanalı, Pınar. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
In this thesis, we investigate path algebras and Leavitt path algebras. Some properties of path and Leavitt path algebras are given. Our aim is to see what conditions on the graph E makes Leavitt path algebras simple. We also study the relations between Incidence algebras and path algebras.
Keywords: Graph theory.